Optimisation of the control policy for a stochastic remanufacturing system with an unreliable replacement parts supply. (22nd January 2010) - Berthaut, Francois; Pellerin, Robert; Gharbi, Ali
We consider the control of a stochastic manufacturing system executing capital assets repair and remanufacturing in a closed-loop system. A simple suboptimal control policy in class of multi-hedging point policy is proposed. This policy consists of inventory thresholds related to different predefined repair and replacement modes, depending on the replacement parts availability. This paper focuses on estimating the optimum control policy parameters in terms of total cost by means of simulation tools. A flexible combined discrete event and continuous modelling is introduced and simulation experiments are conducted for a numerical example to achieve a close approximation of the optimal policy.